Chaos Synchronization of the Fractional Rucklidge System based on New Adomian Polynomials - Wu, Guo-Cheng; Baleanu, Dumitru; Huang, Lan-Lan (Journal of Applied Nonlinear Dynamics, 2026)
The fractional Rucklidge system is a new kind of chaotic models which hold the feature of memory effects and can depict the long history interactions. A numerical formula is proposed by use of the fast Adomian polynomials. Chaotic behavior are discussed and the Poincare sections are given for various fractional cases. It’s also applied in chaos synchronization of the fractional system.